PENGARUH PEMASARAN DIGITAL DAN KUALITAS PRODUK TERHADAP MINAT BELI PELANGGAN PT. HK REALTINDO - Hotman Napitupulu; Sherry Muliawati (Jurnal Ekonomi dan Industri, 2024)
The purpose of this study was to analyze the effect of digital marketing and product quality on customer purchase interest at PT. HK Realtindo. This research is included in the category of causal associative research using a quantitative approach. The population of this research is customers of PT. HK Realtindo, the sampling technique used incidental sampling technique, the number of samples was 80 people. The analytical method uses simultaneous and partially linear regression analysis. The results of the research show that in simultaneous and partially ways digital marketing and product quality have a positive and significant effect on the customer purchase interest at PT. HK Realtindo.